The intelligent mechatronic system for open pit mining to increase the operation life of equipment; E3S Web of Conferences; Vol. 15 : International Innovative Mining Symposium (in memory of Prof. Vladimir Pronoza) - Semykina I. Yu. Irina Yurievna (2017, 2017)
Title screen